International Journal of Air-Conditioning and Refrigeration - Kim, Minsung; Kang, Yong Tae.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
As the only international journal in the field of air-conditioning and refrigeration in Asia, IJACR is dedicated to providing a platform for sharing and disseminating latest research results and information to societies related with air-conditioning and refrigeration. We invite original research papers or comprehensive review articles addressing various aspects of air-conditioning and refrigeration, which includes broad range of applications and underlying theories including fluid dynamics, thermodynamics, heat transfer, and nano/bio-related technologies. Future energy technologies, such as fuel cell, wind turbine, solar cell/heat, geothermal energy are also considered in the journal. (Back issues could be found at www.worldscientific.com/worldscinet/ijacr) Authors can request a support from the partner society to sponsor their Article Processing Charges (APCs) during the process in which they complete the Publishing Agreement with Springer Nature. You can find more details about this process in Journal Updates section. .
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Engineering Thermodynamics, Heat and Mass Transfer